2020
DOI: 10.46505/ijbi.2020.2206
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Kap (Knowledge, Attitude and Practice) of University Students Towards Prevention of Covid-19

Abstract: The present study was aimed to explore the KAP (knowledge, attitude and practice) adopted by the university students of Madhya Pradesh (India) towards prevention of Covid-19 pandemic. For this purpose, authors performed an online survey with 776 students using a selfdesigned semi-structured questionnaire. The results found that students had a moderate to a high level of knowledge about the Covid-19 and sufficient knowledge regarding its preventive measures. The authors could not found any significant correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
(12 reference statements)
1
5
0
Order By: Relevance
“…Most of the students reported always wearing a mask when leaving home in recent days. is is in line with previous studies where most of the study participants reported wearing masks when leaving home [6,10,20]. In other jurisdictions, wearing masks was suboptimal [19].…”
Section: Items (Key)supporting
confidence: 92%
See 1 more Smart Citation
“…Most of the students reported always wearing a mask when leaving home in recent days. is is in line with previous studies where most of the study participants reported wearing masks when leaving home [6,10,20]. In other jurisdictions, wearing masks was suboptimal [19].…”
Section: Items (Key)supporting
confidence: 92%
“…Most of the students have avoided going to crowded places in recent days as a precautionary measure towards the COVID-19 pandemic. is is supported by a previous study in China [12] and India [20] but contradicts another study in the Philippines where a few of the study samples identified avoiding the crowd as a preventive measure [10]. Also, most of the study participants regularly wash their hands as a preventive measure against the COVID-19 pandemic.…”
Section: Items (Key)mentioning
confidence: 56%
“…Similarly, the cross-sectional study carried out by Shabadi et al (13) in Mysuru showed that the median (IQR) knowledge scores among men and women were 5 (4-5) and 5 (4-6), respectively (P = 0.057). Whereas in the study of Sazali et al (20) and Srivastava and Reddy (21), men had a higher median knowledge score [men 78.5 (13.0) vs. women 77.0 (12.0)] and the mean scores respectively (P > 0.05). This deference in our study may be due to more access to electronic gadgets and the internet in men than in women.…”
Section: Discussionmentioning
confidence: 73%
“…The study also reveals that common problems for children were to restriction in their movement and not going to socialize. It also influenced the overall attitude and knowledge of students (Srivastava and Reddy, 2020) [13] . It was also observed during the study children quarantined in administrative quarantine centers might be more susceptible to mental health problems than children's who were quarantined at home because of their higher risk of infection and fear caused by parental separation or separation from their loved ones.…”
Section: Resultsmentioning
confidence: 99%